Synthesis of Al-Based Metal-Organic Framework in Water With Caffeic Acid Ligand and NaOH as Linker Sources With Highly Efficient Anticancer Treatment - Zeraati, Malihe; Rahdar, Abbas; Medina, Dora I.; Sargazi, Ghasem (Frontiers in Chemistry, 2021)
In this study, novel nanostructures of aluminum base metal-organic framework (Al-MOF) samples were synthesized using a sustainable, non-toxic, and cost-effective green synthesis route. Satureja hortensis extract was used as an effective source of linker for the development of the Al-MOF structures. The Fourier-transformed infrared (FTIR) spectrum confirmed the presence of characterization bonds related to the Al-MOF nanostructures synthesized by the green synthesis route. The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analyses revealed that the sample synthesized by Na2-CA was composed of multilayers, although it was agglomerated, but it had dispersed and occurred in spherical particles, indicating active organic matter. N2 adsorption/desorption isotherms demonstrated the significant porosity of the Al-MOF samples that facilitate the high potential of these nanostructures in medical applications. The anticancer treatment of Al-MOF samples was performed with different concentrations using the MTT standard method with untreated cancer cells for 24 and 48 h periods. The results exhibited the significant anticancer properties of Al-MOF samples developed in this study when compared with other MOF samples. Thus, the development of a novel Al-MOF and its application as a natural linker can influence the anticancer treatment of the samples. According to the results, the products developed in this study can be used in more applications such as biosensors, catalysts, and novel adsorbents.